From grass to plastic: The Effects of Economic Development on the Design and Production of the Traditional Swazi Grass Mat Made by Women - Patel, Ramila (My University, 2006)
This research focuses on change and the effects of economic development on the design and production of the traditional grass mat made by women in Swaziland. The visual quality of the traditional Swazi grass mat has transformed. The mat making technique remains unchanged, as does the main raw material in the construction of the mat, but now the traditional grass is accompanied by an artificial element: sweet wrappers, creating shimmering new designs. The technology of making grass mats has been revolutionised with the introduction of the Imbongolo mat-making frame. These changes represent an example of a dynamic art form in the context of the deep-rooted tradition of Swazi material culture. Through interviews with a number of mat-makers and a comprehensive collection of mat samples gathered over an extended period these modifications have been recorded and evaluated in terms of the producers’ response to economic constraints, and the availability of new plastic materials.
Student Number : 9812661N - MA dissertation - School of Art - Faculty of Humanities
Keywords: swazi; grass; mat; plastic; imbongolo